Difficulties Of Beginning Reading and Writing In Lower Primary School Grades And How To Overcome Them - Andelia, Geta; Ahmad, Arifin; Putri, Silfana Nabila; Rahma, Nabilla Aliya; Rahayu, Chitra Sry (Sean Institute, 2024)
This study aims to investigate initial reading and writing difficulties in lower grade elementary school students through a literature review approach. In analyzing this phenomenon, three main research aspects were explored, namely teachers' teaching strategies, factors causing reading difficulties, and the impact of students' lack of interest in learning. The research method applied is literature review, by searching, collecting and analyzing information from various related literature sources. Findings from the literature review show that effective strategies in overcoming reading difficulties include special guidance, attention to student development, and a pleasant learning atmosphere. Factors causing reading difficulties include internal and external aspects, while lack of interest in learning and family support also play a significant role. An in-depth understanding of these literatures makes a valuable contribution to constructing a holistic and in-depth picture of the problem of beginning reading difficulties.